Removal of Congo Red by Silver Carp (Hypophthalmichthys molitrix) Fish Bone Powder: Kinetics, Equilibrium, and Thermodynamic Study - Shahanaz Parvin; Md. Manjur Hussain; Farhana Akter; Biplob Kumar Biswas (Journal of Chemistry)
Powdered form of bones of silver carp fish, an available species in Bangladesh, was investigated as a prominent bioadsorbent for the removal of Congo red from synthetic solution. Experiments were conducted in batch process, and a number of influencing parameters, such as solution pH, adsorbent dosage, contact time, and initial Congo red concentration, were thoroughly investigated for optimization. Kinetic and equilibrium data were well described by pseudo-second-order model and Langmuir isotherm, respectively. Suitability of pseudo-second-order model to best fit with the adsorption process was corroborated by squared sum of errors analysis. Mass transfer mechanism was confirmed by intraparticle pore diffusion and Bangham’s diffusion models. Maximum sorption capacity of fish bone powder was found to be 666.67 mg·g−1. The optimum condition (adsorbent dose: 5 g·L−1; pH: 2.0; operating time: 4 h) for maximum sorption was determined as well. The increasing negative value of Gibbs free energy (ΔG) with temperature rise indicated spontaneous nature and feasibility of adsorption. The positive values of ΔH and ΔS suggested that the adsorption reaction is endothermic and random (at the solid/liquid interface) in nature. The activation energy (29.84 kJ·mol−1) indicated that the sorption process was of physisorption type. A considerably high adsorption capacity pointed towards utilization of this apparently useless biomaterial as an effective adsorbent.